THE EDUCATION ACCORDING TO PAULO FREIRE: FROM PARTICIPATION TO LIBERATION - Agostini, Nilo (2018)
The present study investigates the education according to Paulo Freire in the binomial education and participation, as well as education and liberation from his publications Education, The Practice of Freedom, Pedagogy of the Oppressed and Conscientization: Theory and Practice of Liberation, foundations of his thinking, also taking into account studies about his work and other of his writings. Illiteracy challenges him to seek a new pedagogy, beyond traditional prescriptions. He paves the way for education both as a practice of freedom and as a liberating action. The central axis of his conceptions, conscientization appears, in turn, as a praxis, a process of action and reflection of women and men in history, implying the awakening of their critical awareness, in their human affirmation as subjects committed to the transformation of this same history.